Effects of warming and grazing on soil N availability, species composition, and ANPP in an alpine meadow - Wang, Shiping; Jichuang Duan; Guangping Xu; Yanfen Wang; Zhenhua Zhang; Yichao Rui; Caiyun Luo; Burenbayin Xu; Xiaoxue Zhu; Xiaofeng Chang; Xiaoyong Cui; Haishan Niu; et al. (Ecology (Durham), 2012)
Uncertainty about the effects of warming and grazing on soil nitrogen (N) availability, species composition, and aboveground net primary production (ANPP) limits our ability to predict how global carbon sequestration will vary under future warming with grazing in alpine regions. Through a controlled asymmetrical warming (1.2/1.7Â°C during daytime/nighttime) with a grazing experiment from 2006 to 2010 in an alpine meadow, we found that warming alone and moderate grazing did not significantly affect soil net N mineralization. Although plant species richness significantly decreased by 10% due to warming after 2008, we caution that this may be due to the transient occurrence or disappearance of some rare plant species in all treatments. Warming significantly increased graminoid cover, except in 2009, and legume cover after 2008, but reduced nonâlegume forb cover in the community. Grazing significantly decreased cover of graminoids and legumes before 2009 but increased forb cover in 2010. Warming significantly increased ANPP regardless of grazing, whereas grazing reduced the response of ANPP to warming. N addition did not affect ANPP in both warming and grazing treatments. Our findings suggest that soil N availability does not determine ANPP under simulated warming and that heavy grazing rather than warming causes degradation of the alpine meadows.